1985
DOI: 10.1007/bf02335927
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes in continuously stretched skeletal muscles in sheep

Abstract: The effects of continuous elongation of skeletal muscles were studied on six sheep who underwent a lengthening osteotomy of the right tibia. Open muscle biopsies were taken from the biceps femoris muscle preoperatively (Group A), after 5 weeks of bone distraction (Group B) and after another 5 weeks without further distraction (Group C). The size and distribution of type 1 (slow-twitch) and type 2 (fast-twitch) muscle fibres were determined from sections stained for myofibrillar ATPase activity. All sections we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
2
1

Year Published

1992
1992
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
1
10
2
1
Order By: Relevance
“…Furthermore, it has been demonstrated that lengthening osteotomy might lead to a reduction in the muscle fiber cross-sectional area of Type 2 fibers, but not of Type 1 fibers (Lindboe et al 1985). Our findings are, however, in contrast to those published by Lindboe et al (1985) who showed that a 10-20 percent lengthening osteotomy led to a 44 percent reduction in Type 2 fiber area. These differences may be explained by different experimental conditions.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it has been demonstrated that lengthening osteotomy might lead to a reduction in the muscle fiber cross-sectional area of Type 2 fibers, but not of Type 1 fibers (Lindboe et al 1985). Our findings are, however, in contrast to those published by Lindboe et al (1985) who showed that a 10-20 percent lengthening osteotomy led to a 44 percent reduction in Type 2 fiber area. These differences may be explained by different experimental conditions.…”
Section: Discussioncontrasting
confidence: 99%
“…The degree of shorteninaengthening in our experiment was similiar to that applied in previous experimental studies on limb lengthening by external distraction of the growing bone (Lindboe et al 1985) and in clinical practice in many cases.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…On the other hand, Lindboe et al (1985) reported that, during 10-20 percent bone lengthening, the Type 11 fibers decreased in size, but the Type I fibers did not change in size. They suggested that atrophy of the Type 11 fibers was mainly caused by muscular inactivity during the postoperative period, but an additional effect of continuous stretching of the muscle cannot be excluded.…”
Section: Resultsmentioning
confidence: 97%
“…After long-term denervation, VEGF is still provable in muscles but significantly reduced [6]. Thus muscle atrophy at the distracted side might also be a factor responsible for the relatively high VEGF mRNA levels at the nondistracted side [13, 33,35].…”
Section: Discussionmentioning
confidence: 99%